Perceived stress and coping strategies used by undergraduate dental students: An observational study. - Saira Atif; Nilofar Mustafa; Sarah Ghafoor (PLoS ONE)
Studies around the world have reported that dental students experience higher stress compared to medical students. Prolonged and high perceived stress can be of a significant concern as it affects the personal, psychological, and professional well-being of the student, affecting quality of life. The aim of the study was to describe the perceived stress and coping strategies that undergraduate students at dental schools of Lahore, Pakistan employ. This observational study was conducted in year 2023 to report perceived stress and coping strategies among 720 undergraduate dental students of Lahore using modified Dental Environment Stress (DES) and brief Coping Orientation to Problems Experienced (COPE) questionnaires. Categorical variables such as sex, year of study (year 1 till 4), and responses to DES stress domains, stress-related items, COPE domains, and COPE-related items were computed into frequencies and percentages. Mean item scores of stress domains, stress-related items, COPE domains, and COPE-related items were presented with standard deviations (SD). Groups wise comparisons were done using Mann Whitney U and Kruskal Wallis H tests. P value < 0.05 was considered statistically significant. The majority of the undergraduate dental students perceived moderate amount of stress. Item "overload feeling due to huge syllabus" had the highest mean stress score (3.49±0.76) and "language barrier" had the lowest mean stress score (1.75±0.92). Female students had higher mean stress scores than the male students in all of the DES domains. Mean stress scores were higher in year 4 students for "workload", "self-efficacy beliefs", "faculty and administration", "clinical training", and "social stresses" compared to other years. "Religion" was the highest- and "denial" was the lowest-ranked coping strategies. Female students employed "active coping", "positive reframing", "religion", "venting", "self-blame", "denial", and "behavioral disengagement" coping strategies more than males. Moreover, final year dental students used "instrumental support", "humor", "self-blame", "denial", and "behavioral disengagement" coping strategies more than year 1 and 2 students. Sex and year of study can influence the degree of perceived stress and choice of coping strategies employed to overcome stressful situations. For the emotional, psychological, and professional well-being of undergraduate students, institutions must provide a nurturing and positive learning environment implementing strategies for stress prevention and management.